THE BUKHARA PERFORMANCE STYLE IS A FACTOR IN THE DEVELOPMENT OF MORAL QUALITIES OF TEENAGERS (Academia Science Repository, 2023)
Education of students' moral qualities in the process of music culture lessons of university schools requires continuous musical-pedagogical activity based on a long-term systematized and clear plan.